Alcohol policy process in Malawi: Making it happen - Ferreira-Borges, Carina; Endal, Dag; Babor, Thomas; Dias, Sonia; Kachiwiya, Maganizo; Zakeyu, Nelson (International Journal of Alcohol and Drug Research, 2014)
Ferreira-Borges, C., Endal, D., Babor, T., Dias, S., Kachiwiya, M., & Zakeyu, N. (2014). Alcohol policy process in Malawi: Making it happen. The International Journal Of Alcohol And Drug Research, 3(3), 187 – 192. doi:http://dx.doi.org/10.7895/ijadr.v3i3.156Aims: This paper presents the recent history of alcohol-policy development in Malawi, describing changes in the policy process, initiatives to expand the involvement of relevant stakeholders, and efforts to limit the role and influence of vested commercial interests. We also note the challenges that remain for alcohol-policy formulation in Malawi.Design: We used a holistic, single case-study design to illustrate the process, using information generated from a combination of direct and indirect observations, document reviews, media analysis, and in-depth and semi-structured interviews.Findings: Alcohol policy development in Malawi reflects a complex combination of political and social processes, fraught with numerous stakeholder conflicts and political power plays. Despite the influence of the alcohol industry in the agenda-setting and consultative process, when adequately resourced and supported, civil society organizations can play an important and productive role in steering policy developments in a sound public-interest direction.Conclusions: Documenting this type of practical “natural experiment” provides an important opportunity for learning. The Malawi case study reinforces the need for more regular policy analysis of similar initiatives—in particular, in low-income developing countries—and for additional study of the alcohol-policy development process and policy implementation.